Effect of microporosity on scaffolds for bone tissue engineering. Issue 2 (5th February 2018) - Zhang, Ke; Fan, Yubo; Dunne, Nicholas; Li, Xiaoming
Abstract: Microporosity has a critical role in improving the osteogenesis of scaffolds for bone tissue engineering. Although the exact mechanism, by which it promotes new bone formation, is not well recognized yet, the related hypothesis can be found in many previous studies. This review presents those possible mechanisms about how the microporosity enhances the osteogenic-related functions of cells in vitro and the osteogenic activity of scaffolds in vivo . In summary, the increased specific surface areas by microporosity can offer more protein adsorption sites and accelerate the release of degradation products, which facilitate the interactions between scaffolds and cells. Meanwhile, the unique surface properties of microporous scaffolds have a considerable effect on the protein adsorption. Moreover, capillary force generated by the microporosity can improve the attachment of bone-related cells on the scaffolds surface, and even make the cells achieve penetration into the micropores smaller than them. This review also pays attention to the relationship between the biological and mechanical properties of microporous scaffolds. Although lots of achievements have been obtained, there is still a lot of work to do, some of which has been proposed in the conclusions and perspectives part.